Analiza opinii studentów na temat efektywności reintegracji społecznej osób wykluczonych społecznie = The analysis of students` opinions on the effectiveness of social reintegration of socially excluded people - Antosik-Kot, Nikola (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Social and occupational reintegration interventions aim to help socially excluded people to function effectively at various levels of life. Activities in this area address current problems that arise in small social groups (e.g., family), as well as in broader social and professional contexts.
Keywords: reintegracja społeczna; wykluczenie społeczne; pomoc społeczna; social reintegration; social exclusion; social assistance